Integrated DEA/TOPSIS method in evaluating efficiency and ranking of academic departments of a public university / Nurul lffa Nasuha Abd Rahim ... [et al.] - Abd Rahim, Nurul lffa Nasuha; Md Yunus, Nurhazirah; Mohd Anour, Nurul ‘Ain; Abd Aziz, Nur Azlina (UiTM Cawangan Negeri Sembilan, 2021)
In today's digital world, all higher education institutions face many challenges. The competition is so high that all higher education sectors especially the public universities need to function at their highest level. The reason mainly because public higher education institutions are run on taxpayers’ contributions. Therefore, top management of universities are driven to seek effective strategies for measuring and ranking their academic departments within their institutions. Data Envelopment Analysis (DEA) has been established as an effective method to measure relative efficiency of homogeneous entities known as decision making units (DMUs). Its main advantage is DEA is its ability to manage multiple inputs and outputs. However, standard DEA has some disadvantages and one of them is not being able to discriminate and rank efficient units. Standard DEA can only classify DMUs into two categories namely efficient and inefficient units and consequently, cannot provide full ranking od DMUs. Ranking academic departments are necessary and important for top management of universities so that necessary changes can be made for academic departments to move forward. The Method for Order Preference by Similarity to Ideal Solution (TOPSIS) is a standard decision-making approach with multiple attributes that are commonly used for decision-making. The advantages of the TOPSIS method are it is easy to practice and it allows the best alternative criteria to be obtained in a simple mathematical form. This paper proposed a hybrid approach based on DEA and TOPSIS techniques to overcome the problem of ranking found in standard DEA and applied it to evaluate efficiency and ranking of 22 academic departments of a public university in Malaysia from 2008 to 2010.